2000
DOI: 10.1017/s0317167100052227
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Facet Rhizotomy – Experience with 118 Procedures and Reappraisal of its Value

Abstract: ABSTRACT:Background:There have been many reports of percutaneous radiofrequency facet rhizotomy, perhaps better referred to as facet denervation, usually performed under general anaesthesia, with inconsistent success rates.Objectives:To report the authors' outcome data using both general and local anaesthesia and to reassess the value of this controversial procedure.Methods:Our experience with 118 consecutive percutaneous radiofrequency facet rhizotomies performed on 90 patients in the Toronto Western Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 34 publications
2
50
2
2
Order By: Relevance
“…Radiofrequency at set temperatures of 45°C demonstrated pathological lesions in nerve fibers [2]. Cooled-radiofrequency electrodes have been described for heating large tissue volumes [3]. Increased lesion diameter may improve the likelihood of successful nerve ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency at set temperatures of 45°C demonstrated pathological lesions in nerve fibers [2]. Cooled-radiofrequency electrodes have been described for heating large tissue volumes [3]. Increased lesion diameter may improve the likelihood of successful nerve ablation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Shealy suggested that RF denervation be [10][11][12][13][14][15][16][17][18][19][20]. The authors of the most recent studies have reported success rates ranging widely between 32 and 87% [5][19] [21].…”
Section: Discussionmentioning
confidence: 99%
“…This result is comparable with that achieved in patients without a history of spine surgery. Another possible explanation for reported variations is the involvement of health insurance and worker's compensation issues [7][19] [21].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous radiofrequency lumbar facet denervation was introduced as a treatment for chronic low back pain by Shealy in 1974 [1,3]. Kornick et al [2], however, reported that X-ray fluoroscopy-guided percutaneous radiofrequency denervation of lumbar facets is associated with an overall 1.0% incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous radiofrequency rhizotomy of the medial branch of the posterior rami is used to treat chronic low back pain [1][2][3]. X-ray fluoroscopy-guided percutaneous rhizotomy has been used for spinal pain management for many years.…”
Section: Introductionmentioning
confidence: 99%